Analysis of Preferred Orientations in Linear Friction Welded (LFW) Aluminium Alloy Specimens using "One-shot" Multi-element Energy Dispersive Synchrotron X-ray Diffraction - Xie, M; Jun, T; Korsunsky, A; Drakopoulos, M (2013)
Linear Friction Welding (LFW) has tremendous potential for joining components from similar and dissimilar materials, avoiding material melting and introducing minimal distortion and only moderate levels of residual stress. However, the significant amount of attendant shear introduces preferred crystal orientations that have not yet been well studied. The one-shot approach to the interpretation of multi-element energy-dispersive X-ray powder diffraction data allows preferred orientation analysis without any sample preparation (cutting or polishing) or sample rotation. The key step for texture analysis by X-ray powder diffraction is the derivation of the orientation distribution function (ODF) from experimental data. Matlab toolbox MTEX provides a powerful function calcODF based on the harmonics method for this purpose. In the study reported in this paper, energy dispersive X-ray diffraction patterns were collected using the horseshoe multi-element energy-dispersive Ge detector installed on the JEEP beamline at Diamond Light Source. A single exposure was used for each gauge volume of interest, and a line was scanned across an Aluminum 2024 alloy LFW sample. The patterns were converted into raw pole figures through single peak fitting and equal area projection. The ODF calculation was performed based on these pole figures using Matlab toolbox MTEX. As a result, full pole figures obtained after ODF calculation were obtained. These are presented and discussed. The results show that the thermal-mechanical processes that occur during the LFW process lead to significant modification of the orientation distribution, but cause only moderate changes in the texture index. © 2013 JCPDS-ICDD.